Social Inequalities in Health: Outcomes of Children’s Cochlear Implantation in Lithuania - Stumbrys, Daumantas; Byčkova, Jekaterina; Lesinskas, Eugenijus; Mataitytė-Diržienė, Jurga; Norkūnienė, Jolita (Socialinė teorija, empirija, politika ir praktika, 2020)
The aim of this study was to evaluate the demographic, family, and educational differences in children’s speech perception development after cochlear (hearing) implantation. The research was conducted in Vilnius University Hospital Santaros Klinikos during the years 2013–2018. Open-set speech perception in quiet surroundings were evaluated during hearing assessments (n=81). Information about different factor groups was collected according to the Nottingham Children’s Implant Profile questionnaire. Three main factor groups were analysed: (a) demographic, (b) family, and (c) educational. A Bourdieu-based approach was adopted to analyse social inequalities of health of children with cochlear implants. Different factors were operationalized as different forms of capital. Our findings highlight the importance of family’s social and cultural capital to children speech perception after cochlear implantation.
Keywords: cochlear implants; deaf children; health inequality; Lithuania; speech perception